STUDY OF INTEGRATION OF SAD WARNANING RAJANITI VALUES IN MATHEMATICS LEARNING PROCESS AT ELEVENTH GRADE OF SMA NEGERI 1 SINGARAJA TO SUPPORT ANTI-CORRUPTION GOVERNANCE - ., I Made Yoga Emma Prasetya; ., Prof. Dr.I Nengah Suparta,M.Si; ., Drs. I Nyoman Gita, M.Si (Jurnal Pendidikan Matematika Undiksha, 2014)
Penelitian ini bertujuan untuk mengetahui integrasi Sad Warnaning Rajaniti dalam pembelajaran matematika pada kelas XI SMA Negeri 1 Singaraja dalam mendukung pemerintahan anti-korupsi. Sifat-sifat dalam Sad Warnaning Rajaniti dimodifikasi sesuai dengan nilai-nilai anti-korupsi dan pembelajaran matematika. Sehingga memperoleh indikator-indikator yang digunakan di dalam lembar observasi, angket, dan wawancara. Jenis penelitian ini menggunakan pendekatan kualitatif deskriptif yaitu berasal dari kerangka teori, gagasan para ahli, maupun pengalaman peneliti, dan dikembangkan untuk memperoleh kebenaran dalam bentuk dukungan data empiris lapangan. Subjek penelitian dari penelitian ini adalah guru matematika kelas XI yang terdiri dari tiga guru serta seluruh siswa kelas XI SMA Negeri 1 Singaraja Tahun Ajaran 2013/2014. Siswa kelas XI tersebut terdiri dari kelas XI IA berjumlah 237orang siswa, kelas XI IS berjumlah 9 orang siswa, dan kelas XI IB berjumlah 6 orang siswa. Peneliti meneliti integrasi Sad Waraning Rajaniti dengan melihat pembelajaran yang dilakukan oleh masing-masing guru pengampu di kelas. Data tersebut diperoleh dengan observasi, angket, wawancara, dan studi dokumentasi. Dari hasil penelitian tersebut diperoleh kesimpulan, bahwa pembelajaran matematika di kelas XI IA dan XI IS telah mengintegrasikan Sad Warnaing Rajaniti dengan baik (kategori tinggi) sedangkan pembelajaran matematika yang dilaksanakan di kelas XI IB belum terintegrasi dengan baik (kategori sedang).Kata Kunci : Sad Warnaning Rajaniti, Pembelajaran Matematika, Pemerintahan Anti-korupsi. The purpose of this research was to know the integration process of Sad Warnaning The purpose of this research was to know the integration process of Sad Warnaning Rajaniti values in mathematics learning process at Eleventh Grade of SMAN 1 Singaraja in accordance with the anti-corruption. Characteristics of Sad Warnaning Rajaniti are modified in line with the values of anti-corruption that relevant with mathematics learning for acquiring indicators that use in observation sheets, questionnaire, and interview as instrument of the research. This research was based on qualitative research that using descriptive qualitative sourced from a theory design, idea of the experts and researcher’s comprehension based on experience. All approaches were developed to gain a truth in the form of on field’s empirical data. The subjects of research were mathematics teachers of Eleventh Grade which is consist of different teachers and students of Eleventh Grade of SMAN 1 Singaraja in the academic year 2013/2014. Students of Eleventh Grade consisted of 237 students from science class of eleventh grade, 9 students from social class of eleventh grade, and 6 students from language class of eleventh grade. Researcher was researching the integration of Sad Warnaning Rajaniti by involving in the learning process that conducted by each teacher in the class. That data are acquired by observation, questionnaire, interview, and documentation. The results of research is showed that the integration of Sad Warnaing Rajaniti in science class and social class are good (high category) whereas in language class are fair (medium category).keyword : Warnaning Rajaniti, Mathematics Learning, Anti-Corruption Public.